2007
DOI: 10.1016/j.molcel.2007.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Ribonuclease Dicer Cleaves Triplet Repeat Hairpins into Shorter Repeats that Silence Specific Targets

Abstract: Ribonuclease Dicer functions in cells to excise microRNAs from their precursors and process long double-stranded RNAs into short interfering RNAs. We show that transcripts containing long hairpin structures composed of CNG repeats are another class of Dicer targets. The cellular levels of transcripts from mutant genes involved in triplet repeat expansion diseases such as myotonic dystrophy type 1, Huntington's disease, and spinocerebellar ataxia type 1 are under Dicer control. The Dicer-induced downregulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
171
1
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(185 citation statements)
references
References 38 publications
(49 reference statements)
7
171
1
6
Order By: Relevance
“…It is also known that MBNL1 interacts mainly with the GC element of the repeated sequence (45). The structural similarity of all CNG repeat hairpins was also observed in the in vitro assay with ribonuclease Dicer (46). On the other hand, these hairpin structures are different targets for the binding of small molecule ligands (47,48).…”
Section: Discussionmentioning
confidence: 79%
“…It is also known that MBNL1 interacts mainly with the GC element of the repeated sequence (45). The structural similarity of all CNG repeat hairpins was also observed in the in vitro assay with ribonuclease Dicer (46). On the other hand, these hairpin structures are different targets for the binding of small molecule ligands (47,48).…”
Section: Discussionmentioning
confidence: 79%
“…18,20,24 It has also been shown that long CUG repeats degrade, resulting in the accumulation of short CUG repeats detectable in DM1 cells. 42 Because the accumulation of short CUG repeats causes the DM1 phenotype in DM1 murine models, 24 we decided to determine whether high levels of short CUG repeats would elevate CUGBP1. Analysis of CUGBP1 expression after a single pulse of transcription of CUG 25 showed that CUGBP1 is elevated in cytoplasm at 7 hours after Dox addition ( Figure 4A).…”
Section: Cugbp1 Elevation Is a Primary Event Of The Accumulation Of Tmentioning
confidence: 99%
“…Nonviral approaches to reduce CUG exp RNA include short interfering RNA (siRNA), which has demonstrated efficacy in DM1 fibroblasts. 64 Together, these data support a role for degradation of the mutant RNA as a potential therapeutic strategy in DM1. Clinical application of these strategies necessitate development of efficient means of systemic delivery of viral-mediated antisense, siRNA, or both.…”
Section: Reduction Of Rna-mediated Toxicitymentioning
confidence: 77%